PHYSICOCHEMICAL CHARACTERS OF WATER AS BREEDING SITE OF Aedes spp. IN PAYAMAN LAMONGAN - Fita Fitriatul Wahidah; Trisnan Alif (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2022)
Abstract Dengue hemorrhagic fever (DHF) is a disease that is a problem in society. Lamongan Regency has been declared a DHF KLB (Extraordinary Event) with a number of 86 cases in 2015. The village with the highest incidence of DHF in Lamongan Regency is Payaman Village. This study aims to analyze the physical and chemical factors of the water used as a breeding ground for Aedes spp. This research is a descriptive study with a cross sectional approach. Sampling was carried out in 50 houses located in Payaman Village, Solokuro, Lamongan district. The research parameters there are volume of water, temperature, pH, value of water turbidity (NTU), and DO value. The results showed that each type of container has different physical and chemical properties of water. The highest volume of water is in the bathtub type with an average water volume of 152,500 ml. While the least was in the axillary types of Musa paradisiaca (185 ml) and Colocasia esculenta (177 ml). The average water temperature at the breeding site ranges from 25-30oC. The acidity of the water ranges from 6-7. The value of DO levels ranged from 5-8.5 ppm. The value of water turbidity ranges from 4.50-25 NTU with an average of 15.31 NTU. Keywords: physicochemical, breeding ste, Aedes spp., Payaman, Lamongan